Match & player analysis in soccer: Computer coding and analytic possibilities - Anguera-Argilaga, M. T.; Blanco-Villasenor, A.; Losada-Lopez, J. L.; Arda-Suarez, T.; Camerino Foguet, O.; Castellano-Paulis, J.; Hernandez-Mendo, A.; Jonsson, G. (International Journal of Computer Science in Sport, 2002)
In team sports, especially in soccer, there is a certain complexity in the interaction between variables (players), variables of execution (displacements, lacks that will give place to regulation interruptions, throw, ball losses, recoveries, passes, etc.), and contextual variables (area of reception of the ball, area of pass of the ball, duration of the actions, etc.).